Manfaat Bakso Jantung Pisang untuk Ibu Menyusui - Yusni Igirisa; Yusni Podungge; Siti Choirul Dwi Astuti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Breastmilk production runs smoothly. Breastfeeding mothers must eat sufficient nutrition. A good food ingredient for breastfeeding mothers is the banana heart because it contains galactagogue which can stimulate the hormones oxytocin and prolactin to increase milk production. The banana heart is also easily available by the community for daily use. To increase the consumption of banana blossoms in nursing mothers, it is processed into food in the form of meatballs. Meatballs are a national food that is popular with all people. The method of processing meatballs is also easy and provides many benefits for the health of the body. This research has the aim, benefits, of banana heart meatball for breastfeeding mother's milk production. This type of research is quasi-experimental with a pretest and posttest approach. A sample of 60 mothers breastfed for more than the first day in the working area of ​​Bone Bolango Health Center, Gorontalo. The sampling technique used purposive sampling. Measuring instruments used measuring cups and observation sheets. Before being given the treatment, the respondents' milk was given 100 grams of heart meatballs every day for 6 days. After that, it is measured again with a measuring cup and an observation sheet. The results of data analysis used paired t-test values ​​(p-value 0.001 <α = 0.05) in the breast milk production group in the case and treatment control groups. The result is an average increase in milk production after the 24 ml treatment.